2020
DOI: 10.1186/s12891-020-03414-y
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of throwing exercise with TheraBand in male volleyball players with shoulder internal rotation deficit: a randomized controlled trial

Abstract: Background The Glenohumeral internal-rotation deficit (GIRD) is related to the altered eccentric external-rotator (ER), the concentric internal-rotator (IR), muscle strength, and the ER: IR ratio. GIRD has been documented as a risk factor for shoulder injuries. However, few studies have investigated the effect of an exercise training on these parameters in athletes with GIRD. Therefore, the purpose of this study was to evaluate the effects of an 8-week throwing exercise with a TheraBand for ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 28 publications
0
37
0
1
Order By: Relevance
“…Schneider, et al [2] reported that shoulder-humerus isometric strength response to 60-90° angular degree may be different in volleyball players. Moradi, et al [5] examined that one threband exercise for throwing performance efficiency per week strengthening section 0.001; d = 1.84 high effect). Other significant difference the pre test (p < 0.014; d = 0.62 high effect) was found in the 90° angular degree in the dominant arm of FST group and again FST group (p < 0.001; d = 2.06 highly effect size) in the post test.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Schneider, et al [2] reported that shoulder-humerus isometric strength response to 60-90° angular degree may be different in volleyball players. Moradi, et al [5] examined that one threband exercise for throwing performance efficiency per week strengthening section 0.001; d = 1.84 high effect). Other significant difference the pre test (p < 0.014; d = 0.62 high effect) was found in the 90° angular degree in the dominant arm of FST group and again FST group (p < 0.001; d = 2.06 highly effect size) in the post test.…”
Section: Resultsmentioning
confidence: 99%
“…Because the external resistive load rejects the same working force in different regions of the force. For this reason, the athlete should awareness of heat and power changes during repetition and rest in the individual shoulder and hand-raising movements [3,5,18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This training was based on the standardization of the protocols and the identification of execution errors. Prior to the evaluation of the upper extremity functional performance tests, a 5-min warm-up was carried out, consisting of static stretching exercises (two stretches per muscle) for the shoulder complex muscles (upper trapezius, shoulder rotator muscles, biceps brachii, triceps brachii, and pectoralis major), as this type of stretching has not been shown to influence the repositioning accuracy of joint position sense ( Moradi et al, 2020 ; Torres, Duarte & Cabri, 2012 ).…”
Section: Methodsmentioning
confidence: 99%